Q: X plus 4.3 x equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

x+27=43 x+27-27=43-27 x+0=16

X equals 6 ..

3x+2y=43 where x=(-4+y)/2 =0.5y-2 3(0.5y-2)+2y=43 1.5y-6+2y=43 3.5y-6=43 3.5y=49 y=49/3.5 which is the same as (49x2)/7 =14

x=6=x=5+x=13+x=20 x cannot = x+5. This question has no answer.

Related questions

2x + 15 = 8x + 43 -6x = 28 x = -6 / 28 = -3 / 14

x+27=43 x+27-27=43-27 x+0=16

x=7

X equals 6 ..

3x+2y=43 where x=(-4+y)/2 =0.5y-2 3(0.5y-2)+2y=43 1.5y-6+2y=43 3.5y-6=43 3.5y=49 y=49/3.5 which is the same as (49x2)/7 =14

x=6=x=5+x=13+x=20 x cannot = x+5. This question has no answer.

x + 6

76= -43 + X add 43 to both sides 76 + 43 = -43 + 43 + x 119 = x

X equals 9.

(x, y) = (-6, 0)

if -4x+6=38 what x=

x=12 because 12 over 6 is 2,and 2 plus 4 is 6.